29.9k views
4 votes
Solve for b. Put your answer in simplest radical form. Show Steps plz!

A = 4πbc + πb^2

User Jjude
by
5.7k points

1 Answer

3 votes

Answer:

b = -2c ± [√(4π²c² + πA)]/π

Explanation:

A = 4πbc + πb^2

A = 4πbc + πb²

πb² + 4πbc - A = 0

Using the quadratic formula to solve this quadratic equation.

The quadratic formula for the quadratic equation, pb² + qb + r = 0, is given as

b = [-q ± √(q² - 4pr)] ÷ 2p

Comparing

πb² + 4πbc - A = 0 with pb² + qb + r = 0,

p = π

q = 4πc

r = -A

b = [-q ± √(q² - 4pr)] ÷ 2p

b = {-4πc ± √[(4πc)² - 4(π)(-A)]} ÷ 2π

b = {-4πc ± √[16π²c² + 4πA]} ÷ 2π

b = (-4πc/2π) ± {√[16π²c² + 4πA] ÷ 2π}

b = -2c ± [√(4π²c² + πA)]/π

Hope this Helps!!!

User Xochitl
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.